Determination of the sign of the decay width difference in the B0s system - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Britsch, Markward; Blouw, Johan; Dordei, Francesca; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Jäger, Andreas; Kreplin, Katharina; Krocker, Georg Alexander; et al. (Physical review letters, 2012)
The interference between the K+K− S-wave and P-wave amplitudes in B0s→J/ψK+K− decays with the K+K− pairs in the region around the ϕ(1020) resonance is used to determine the variation of the difference of the strong phase between these amplitudes as a function of K+K− invariant mass. Combined with the results from our CP asymmetry measurement in B0s→J/ψϕ decays, we conclude that the B0s mass eigenstate that is almost CP=+1 is lighter and decays faster than the mass eigenstate that is almost CP=−1. This determines the sign of the decay width difference ΔΓs≡ΓL−ΓH to be positive. Our result also resolves the ambiguity in the past measurements of the CP violating phase ϕs to be close to zero rather than π. These conclusions are in agreement with the standard model expectations.
Gesehen am 31.10.2018
R. Aaij, S. Bachmann, A. Bien, J. Blouw, M. Britsch, F. Dordei, F. Eisele, C. Faerber, S. Hansmann-Menzemer, A. Jaeger, K. Kreplin, G. Krocker, P. Krokovny, C. Langenbruch, C. Linn, J. Marks, M. Meissner, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, S. Wandernoth, D. Wiedner, A. Zhelezov [und weitere] (LHCb Collaboration)